2017
DOI: 10.1016/j.jsams.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Motor competence and characteristics within the preschool environment

Abstract: Objectives Environmental characteristics within preschools that influence children’s motor competence are largely unknown. The purpose of the present study was to examine the contribution of various preschool environmental characteristics to children’s locomotor, object control, and total gross motor scores. Design Cross-sectional, observational study of 3–5 year-old children (n = 229) from 22 preschools in South Carolina. Methods The Children’s Activity and Movement in Preschool Study (CHAMPS) Motor Skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 21 publications
(24 reference statements)
1
37
2
8
Order By: Relevance
“…The level and intensity of physical activity could be increased through different interventions, even in indoor settings [ 39 ]. It is necessary to point out the results of this and similar research, that the frequency of going out significantly increases the level of motor competences and locomotion [ 40 ]. It has also been confirmed that providing the ability to use portable play equipment and short training of educators can contribute to a higher level of locomotion of children in daycare [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level and intensity of physical activity could be increased through different interventions, even in indoor settings [ 39 ]. It is necessary to point out the results of this and similar research, that the frequency of going out significantly increases the level of motor competences and locomotion [ 40 ]. It has also been confirmed that providing the ability to use portable play equipment and short training of educators can contribute to a higher level of locomotion of children in daycare [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, attention should be paid to girls and their physical activity should be stimulated, as it was found that they were less active throughout the day and during their stay in the institution. Another explanation for gender differences could be the fact that girls showed lower motor competence than boys in this age group [ 40 ], and motor competence is strongly associated with physical activity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor to consider in the educational environment is the teacher. One study found that a higher percentage of classroom teachers with a college degree was related to the better total motor performance and locomotor performance of 3–6-year-old children but not to object control performance [ 58 ]. Another study looked at classroom activity interactions, which were conceptualized as one variable composed of the amount of supervision, discipline, interaction between teacher and child, and interaction between children [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies, investigating the same study sample, found no relationship [ 34 , 35 ], while another study found a relationship but did not define the direction of the relationship [ 48 ]. Previous research suggests that a higher number of students in a class might be related to poorer motor skills, because the available resources such as space to move around and teachers’ time and attention are more diluted [ 58 , 80 ]. However, a review has shown that the effect of class size on other domains such as academic achievement is small at best [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…En este desarrollo, por tanto, juega un papel crucial la Educación Infantil, debido a que es el primer periodo de educación institucionalizada, donde la motricidad comienza su desarrollo (Bornstein, Hahn, & Suwalsky, 2013;Inverson, 2010). Por tanto, es fundamental que desde el ámbito educativo se ofrezca a los niños diferentes medios que les ayuden a establecer distintas habilidades motrices básicas que seguirán siendo desarrolladas a lo largo de la infancia (True et al, 2017). Así, los niños podrán lograr una competencia motriz adecuada, la cual también es fundamental para el desarrollo cognitivo y social de éstos (Morrison, 2005).…”
Section: Introductionunclassified